Preparation method of polymorphic starch nanoparticles
By using the angle control of mechanical shear force and paddle stirrer during the alkaline gelatinization process, multi-morphological starch nanoparticles were prepared, which solved the problem of difficulty in morphological control in the prior art and improved drug delivery and Application performance in food science.
Patent Information
- Application Number
- CN202411479865.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing preparation methods for starch nanoparticles are difficult to control the morphology, especially non-spherical starch nanoparticles are difficult to produce stably in drug delivery and food science, and cannot meet the needs of different application scenarios.
After alkaline gelatinizing starch, mechanical shear force is applied during the rearrangement process, and the angle control of the blades of the paddle stirrer and the rotation shaft is controlled by the angle of the rod, ellipsoidal and spindle-shaped starch nanometers in various shapes. Granules.
The controllable preparation of multi-morphological starch nanoparticles has been realized, which has expanded its application scenarios, improved drug load capacity and release characteristics, and improved dispersion and stability in the food system.
Smart Images

Figure CN118994653B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing starch nanoparticles, in particular to a method for preparing polymorphic starch nanoparticles. Background Art
[0002] Starch nanoparticles (SNPs) have become a green nanomaterial that has attracted much attention due to their unique physicochemical properties, such as wide sources, high specific surface area, good biodegradability and biocompatibility. SNPs have shown broad application prospects in many fields, such as drug delivery, food science, smart food packaging, cosmetic stabilizers, and bioimaging.
[0003] At present, the preparation of SNPs mainly relies on two major technical strategies: "top-down" and "bottom-up". "Top-down" strategy: This strategy degrades larger starch particles into nanoscale by physical or chemical means. Commonly used techniques include ball milling, high-pressure homogenization, ultrasonic treatment, gamma irradiation, acid hydrolysis, and enzymatic hydrolysis. Although these methods can effectively reduce the particle size, it is difficult to accurately control the final morphology and size distribution of the particles because they are gradually degraded from larger particles, resulting in a wide distribution of product particle sizes and different morphologies. "Bottom-up" strategy: This strategy starts from monomers or small molecules and constructs nanoparticles by self-assembly or chemical synthesis. Commonly used methods include nanoprecipitation, emulsion cross-linking, recrystallization, etc. Among them, the nanoprecipitation method is particularly worthy of attention because it can be physically screened based on the principle of like dissolves like by adding anti-solvents such as ethanol, thereby improving the uniformity of the product to a certain extent.
[0004] Although the above methods provide multiple ways to prepare SNPs, there are still some urgent problems to be solved in practical applications. Current technologies are mainly limited to the preparation of spherical SNPs, and their morphology cannot be effectively controlled to meet the needs of different application scenarios. For example: Drug delivery: Non-spherical SNPs (such as flakes or rods) may have higher drug loading capacity and more controllable release characteristics, but existing technologies make it difficult to stably produce SNPs with these special morphologies. Food science: In the food industry, the morphology of nanoparticles also affects their dispersibility and stability in food systems. Spherical SNPs may not be sufficient to meet the requirements of certain food formulations, especially those applications that require enhanced mechanical properties or improved sensory properties. Summary of the invention
[0005] To solve the above problems, the present invention provides a method for preparing polymorphic starch nanoparticles, which forms polymorphic starch nanoparticles under the action of mechanical shear force in the rearrangement process after alkali-heat gelatinization of starch. The polymorphic starch nanoparticles are rearranged into different forms under different shear forces, thereby expanding the application scenarios of nano starch particles.
[0006] In order to achieve the above invention, the technical solution of the present application is as follows: A method for preparing polymorphic starch nanoparticles comprises the following steps:
[0007] (1) Disperse 5 g of starch in 100 mL of 0.5 M sodium hydroxide solution for gelatinization in a water bath and cool to room temperature to form a starch cluster solution;
[0008] (2) subjecting the starch cluster solution to alcohol precipitation to form a polymorphic starch nanoparticle precursor solution;
[0009] (3) using a paddle stirrer to stir and rearrange the mixture to obtain a purified polymorphic starch nanoparticle solution, thereby inducing the polymorphic starch nanoparticle precursor solution to undergo starch chain rearrangement, thereby achieving the purpose of purifying the system; Figure 3 The angle a between the midline of the paddle of the paddle stirrer and the plane perpendicular to the axis of rotation is 30°. Figure 4 , the angle b between the blade plane and the plane perpendicular to the rotation axis is 30~90°, and the stirring speed is 200~1500 rpm;
[0010] The blades of the paddle agitator of the present application can be adjusted by replacing different blades to achieve angle adjustment of angle a and angle b, and angle a and angle b can be upward or downward, that is, the angle above or below the plane perpendicular to the rotation axis.
[0011] (4) The purified polymorphic starch nanoparticle solution is centrifuged, the precipitate is washed with anhydrous ethanol and centrifuged again to obtain a final precipitate to remove soluble molecules and alkaline solvents, the final precipitate is freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles.
[0012] Furthermore, the starch is one or more of corn starch, rice starch, wheat starch, sweet potato starch, cassava starch, sweet potato starch, and potato starch.
[0013] Furthermore, the water bath gelatinization conditions are as follows: the sodium hydroxide solution of starch is placed in a water bath at 65-95° C., while the magnetic stirring speed is maintained at 200-800 rpm.
[0014] Furthermore, the alcohol precipitation treatment is as follows: anhydrous ethanol is dripped into the starch cluster solution at a rate of 5-30 mL / min, the volume ratio of anhydrous ethanol to the starch cluster solution is 1:1, and the stirring speed is maintained at 200-1500 rpm during the alcohol precipitation treatment.
[0015] Furthermore, the centrifugation conditions are: centrifugal speed is 4000-8000 rpm, and the centrifugal time is 10-20 min.
[0016] Furthermore, the freeze-drying treatment conditions are: vacuum drying at -60~-40°C.
[0017] Furthermore, the conditions for the grinding and sieving are: grinding with a grinder at 15000 rpm for 90 seconds.
[0018] Furthermore, the strip-shaped starch nanoparticles are one of rod-shaped, ellipsoidal, and spindle-shaped. The angle between the blade plane and the plane perpendicular to the rotation axis is 72~90° to produce rod-shaped strip-shaped starch nanoparticles, the angle between the blade plane and the plane perpendicular to the rotation axis is 51~69° to produce ellipsoidal strip-shaped starch nanoparticles, and the angle between the blade plane and the plane perpendicular to the rotation axis is 30~48° to produce spindle-shaped strip-shaped starch nanoparticles.
[0019] The beneficial effects of the present invention are:
[0020] By controlling the angle between the midline of the paddle blade of the paddle stirrer and the plane perpendicular to the rotating axis and the angle between the paddle blade of the paddle stirrer and the plane perpendicular to the rotating axis, controllable preparation and purification of polymorphic strip starch nanoparticles are achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a flow chart of a method for preparing polymorphic starch nanoparticles of the present invention;
[0022] Figure 2 A three-dimensional diagram of a blade of a paddle stirrer used in the present invention;
[0023] Figure 3 A schematic diagram of the angle between the center line of the blade of a paddle stirrer and the plane perpendicular to the rotation axis;
[0024] Figure 4 A schematic diagram of the angle between the blade plane of a paddle stirrer and the plane perpendicular to the rotation axis;
[0025] Figure 5 This is a SEM image of the rod-shaped starch nanoparticles of Example 1;
[0026] Figure 6 This is a SEM image of the ellipsoidal strip-shaped starch nanoparticles of Example 1;
[0027] Figure 7 This is a SEM image of the spindle-shaped starch nanoparticles of Example 1;
[0028] Figure 8 This is a particle size distribution diagram of the rod-shaped starch nanoparticles of Example 1;
[0029] Fig. 9 This is a particle size distribution diagram of the ellipsoidal strip-shaped starch nanoparticles of Example 1;
[0030] Fig.10 This is a particle size distribution diagram of the spindle-shaped strip-shaped starch nanoparticles of Example 1;
[0031] Fig.11 This is the XRD pattern of the rod-shaped starch nanoparticles of Example 1;
[0032] Fig.12 This is the XRD pattern of the ellipsoidal strip-shaped starch nanoparticles of Example 1;
[0033] Fig.13 This is the XRD pattern of the spindle-shaped starch nanoparticles of Example 1;
[0034] Fig.14 This is a SEM image of the rod-shaped starch nanoparticles of Example 2;
[0035] Fig.15 This is a SEM image of the ellipsoidal strip-shaped starch nanoparticles of Example 2;
[0036] Fig.16 This is a SEM image of the spindle-shaped starch nanoparticles of Example 2;
[0037] Fig.17 This is a particle size distribution diagram of the rod-shaped starch nanoparticles of Example 2;
[0038] Fig.18 This is a particle size distribution diagram of the ellipsoidal strip-shaped starch nanoparticles of Example 2;
[0039] Fig.19 This is a particle size distribution diagram of the spindle-shaped strip-shaped starch nanoparticles of Example 2;
[0040] Fig. 20 This is the XRD pattern of the rod-shaped starch nanoparticles of Example 2;
[0041] Fig.21 This is the XRD pattern of the ellipsoidal strip-shaped starch nanoparticles of Example 2;
[0042] Fig. 22 This is the XRD pattern of the spindle-shaped strip-shaped starch nanoparticles of Example 2;
[0043] Fig.23 This is a SEM image of the rod-shaped starch nanoparticles of Example 3;
[0044] Fig.24 This is a SEM image of the ellipsoidal strip-shaped starch nanoparticles of Example 3;
[0045] Fig.25 This is a SEM image of the spindle-shaped starch nanoparticles of Example 3;
[0046] Fig.26 This is a particle size distribution diagram of the rod-shaped starch nanoparticles of Example 3;
[0047] Fig. 27 This is a particle size distribution diagram of the ellipsoidal strip-shaped starch nanoparticles of Example 3;
[0048] Fig.28 This is a particle size distribution diagram of the spindle-shaped strip-shaped starch nanoparticles of Example 3;
[0049] Fig.29 This is the XRD pattern of the rod-shaped starch nanoparticles of Example 3;
[0050] Fig.30 This is the XRD pattern of the ellipsoidal strip-shaped starch nanoparticles of Example 3;
[0051] Fig.31 This is the XRD pattern of the spindle-shaped strip-shaped starch nanoparticles of Example 3;
[0052] Fig.32 This is the SEM image of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 1;
[0053] Fig.33 This is a particle size distribution diagram of the mixed system of multi-morphological strip-shaped nano starch particles in Comparative Example 1;
[0054] Fig.34 The XRD diagram of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 1;
[0055] Fig.35 This is the SEM image of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 2;
[0056] Fig.36 This is a particle size distribution diagram of the mixed system of multi-morphological strip-shaped nano starch particles in Comparative Example 2;
[0057] Fig.37 The XRD diagram of the mixed system of multi-morphological strip-shaped nano starch particles in Comparative Example 2;
[0058] Fig.38This is the SEM image of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 3;
[0059] Fig.39 This is a particle size distribution diagram of the mixed system of multi-morphological strip-shaped nano starch particles in Comparative Example 3;
[0060] Fig.40 The XRD diagram of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 3;
[0061] Fig.41 This is the SEM image of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 4;
[0062] Fig.42 This is a particle size distribution diagram of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 4;
[0063] Fig.43 This is the XRD diagram of the mixed system of multi-morphological strip-shaped nano starch particles of Comparative Example 4;
[0064] In this application, the scale bar of all SEM images is 300 nm;
[0065] Among them, a is the angle between the center line of the paddle blade of the paddle stirrer and the plane perpendicular to the rotation axis, and b is the angle between the paddle blade plane of the paddle stirrer and the plane perpendicular to the rotation axis. DETAILED DESCRIPTION
[0066] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0067] The present application achieves controllable preparation and purification of polymorphic strip starch nanoparticles by controlling the angle between the midline of the paddle blade of the paddle stirrer and the plane perpendicular to the rotation axis and the angle between the paddle blade of the paddle stirrer and the plane perpendicular to the rotation axis.
[0068] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0069] Example 1
[0070] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0071] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of corn starch was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0072] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0073] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0074] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0075] The morphology and structure of the prepared samples were characterized as follows:
[0076] (1) Morphological observation: The obtained strip-shaped starch nanoparticles were passed through a 200-mesh sieve. 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. The suspension was evenly dispersed using a homogenizer and then dropped onto a silicon wafer fixed on a copper stand. After natural drying, the suspension was subjected to gold spraying. The surface morphology of the sample was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3 KV. Figure 5 .
[0077] (2) Particle size measurement: The obtained strip-shaped starch nanoparticles were sieved through a 200-mesh sieve, and 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. After being dispersed evenly using a homogenizer, the particle size distribution of the starch nanoparticles was measured using a nanoparticle size analyzer (DLS). Figure 8 ;
[0078] (3) Crystal structure characterization: The obtained starch nanoparticle powder was subjected to XRD scanning at 40 kV and 50 mA using Cu Kα radiation (λ = 0.1542 nm). Fig.11 .
[0079] The angles between the blade plane and the plane perpendicular to the rotation axis were changed to 69° and 48° respectively, and then the above steps (1) to (4) were repeated. The morphology and structure of the sample were then observed. The SEM results are shown in Figure 2. Figure 6 and Figure 7 The particle size distribution results are as follows Fig. 9 and Fig.10 , XRD results are as follows Fig.12 and Fig.13 .
[0080] The starch nanoparticles prepared in this embodiment are Figure 5 , Figure 6 , Figure 7 SEM images and Figure 8 , Fig. 9 , Fig.10 The particle size distribution diagram showing a bimodal characteristic in the figure shows that strip-shaped starch nanoparticles were obtained under different rearrangement conditions, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The particles formed under the stirring rearrangement conditions of 69° and 48° were rod-shaped, ellipsoid-shaped, and spindle-shaped, respectively. Fig.11 , Fig.12 , Fig.13 It can be seen from the XRD images of the strip-shaped starch nanoparticles in each form that the crystallization peaks are more obvious than those in Comparative Example 4, indicating that the rearrangement treatment optimizes the crystal structure; and compared with Comparative Example 1, Comparative Example 2, and Comparative Example 3, this embodiment Figure 5 , Figure 6 , Figure 7 There are no mixed particles in the background of the SEM image, which makes it have a more compact crystalline structure.
[0081] Example 2
[0082] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0083] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of corn starch was dispersed in the sodium hydroxide solution and placed in an 80 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 500 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0084] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 15 mL / min, and the stirring speed was maintained at 1000 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0085] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 81°. The stirring speed was maintained at 1000 rpm during the process;
[0086] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 6000 rpm for 15 min; the conditions for the freeze-drying treatment were: vacuum drying at -50°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0087] The morphology and structure of the prepared samples were characterized as follows:
[0088] (1) Morphological observation: The obtained strip-shaped starch nanoparticles were passed through a 200-mesh sieve. 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. The suspension was evenly dispersed using a homogenizer and then dropped onto a silicon wafer fixed on a copper stand. After natural drying, the suspension was subjected to gold spraying. The surface morphology of the sample was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3 KV. Fig.14 .
[0089] (2) Particle size measurement: The obtained strip-shaped starch nanoparticles were sieved through a 200-mesh sieve, and 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. After being dispersed evenly using a homogenizer, the particle size distribution of the starch nanoparticles was measured using a nanoparticle size analyzer (DLS). Fig.17 ;
[0090] (3) Crystal structure characterization: The obtained starch nanoparticle powder was subjected to XRD scanning at 40 kV and 50 mA using Cu Kα radiation (λ = 0.1542 nm). Fig. 20 .
[0091] The angles between the blade plane and the plane perpendicular to the rotation axis were changed to 60° and 39° respectively, and then the above steps (1) to (4) were repeated. The morphology and structure of the sample were then observed. The SEM results are shown in Figure 2. Fig.15 and Fig.16 The particle size distribution results are as follows Fig.18 and Fig.19 , XRD results are as follows Fig.21 and Fig. 22 .
[0092] The starch nanoparticles prepared in this embodiment are Fig.14 , Fig.15 , Fig.16 SEM images and Fig.17 , Fig.18 , Fig.19 The particle size distribution diagram showing a bimodal characteristic in the figure shows that strip-shaped starch nanoparticles were obtained under different rearrangement conditions, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 81°. The particles formed under the stirring rearrangement conditions of 60° and 39° were rod-shaped, ellipsoid-shaped, and spindle-shaped, respectively. Fig. 20 , Fig.21 , Fig. 22 It can be seen from the XRD images that the strip-shaped starch nanoparticles in each form have more obvious crystallization peaks than those in Comparative Example 4, indicating that the rearrangement treatment optimizes its crystal structure.
[0093] Example 3
[0094] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0095] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of corn starch was dispersed in the sodium hydroxide solution and placed in a 65 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 800 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0096] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 5 mL / min, and the stirring speed was maintained at 200 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0097] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 72°. The stirring speed was maintained at 200 rpm during the process;
[0098] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 4000 rpm for 20 min; the conditions for the freeze-drying treatment were: vacuum drying at -40°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0099] The morphology and structure of the prepared samples were characterized as follows:
[0100] (1) Morphological observation: The obtained strip-shaped starch nanoparticles were passed through a 200-mesh sieve. 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. The suspension was evenly dispersed using a homogenizer and then dropped onto a silicon wafer fixed on a copper stand. After natural drying, the suspension was subjected to gold spraying. The surface morphology of the sample was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3 KV. Fig.23 .
[0101] (2) Particle size measurement: The obtained strip-shaped starch nanoparticles were sieved through a 200-mesh sieve, and 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. After being dispersed evenly using a homogenizer, the particle size distribution of the starch nanoparticles was measured using a nanoparticle size analyzer (DLS). Fig.26 ;
[0102] (3) Crystal structure characterization: The obtained starch nanoparticle powder was subjected to XRD scanning at 40 kV and 50 mA using Cu Kα radiation (λ = 0.1542 nm). Fig.29 .
[0103] The angles between the blade plane and the plane perpendicular to the rotation axis were changed to 51° and 30° respectively, and then the above steps (1) to (4) were repeated. The morphology and structure of the sample were then observed. The SEM results are shown in Figure 2. Fig.24 and Fig.25 The particle size distribution results are as follows Fig. 27 and Fig.28 , XRD results are as follows Fig.30 and Fig.31 .
[0104] The starch nanoparticles prepared in this embodiment are Fig.23 , Fig.24 , Fig.25 SEM images and Fig.26 , Fig. 27 , Fig.28 The particle size distribution diagram showing a bimodal characteristic in the figure shows that strip-shaped starch nanoparticles were obtained under different rearrangement conditions, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 72°. The particles formed under the stirring rearrangement conditions of 51° and 30° were rod-shaped, ellipsoid-shaped, and spindle-shaped, respectively. Fig.29 , Fig.30 , Fig.31 It can be seen from the XRD images that the strip-shaped starch nanoparticles in each form have more obvious crystallization peaks than those in Comparative Example 4, indicating that the rearrangement treatment optimizes its crystal structure.
[0105] Example 4
[0106] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0107] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of rice starch was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0108] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0109] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0110] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0111] Example 5
[0112] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0113] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of wheat starch was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0114] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0115] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0116] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0117] Example 6
[0118] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0119] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of sweet potato starch was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0120] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0121] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0122] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0123] Example 7
[0124] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0125] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of cassava starch was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0126] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0127] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0128] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0129] Example 8
[0130] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0131] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of sweet potato starch was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% mass volume ratio starch cluster solution;
[0132] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0133] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0134] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0135] Example 9
[0136] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0137] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of potato starch was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0138] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0139] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0140] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0141] Example 10
[0142] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0143] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 1 g of corn starch, 1 g of rice starch, 1 g of wheat starch, 1 g of sweet potato starch, and 1 g of cassava starch were dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0144] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0145] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 90°. The stirring speed was maintained at 1500 rpm during the process;
[0146] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0147] In certain embodiments, other starch combinations may also be used.
[0148] Comparative Example 1
[0149] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0150] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of corn starch (dry basis) was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0151] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0152] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 70°. The stirring speed was maintained at 1500 rpm during the process;
[0153] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0154] The morphology and structure of the prepared samples were characterized as follows:
[0155] (1) Morphological observation: The obtained strip-shaped starch nanoparticles were passed through a 200-mesh sieve. 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. The suspension was evenly dispersed using a homogenizer and then dropped onto a silicon wafer fixed on a copper stand. After natural drying, the suspension was subjected to gold spraying. The surface morphology of the sample was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3 KV. Fig.32 .
[0156] (2) Particle size measurement: The obtained strip-shaped starch nanoparticles were sieved through a 200-mesh sieve, and 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. After being dispersed evenly using a homogenizer, the particle size distribution of the starch nanoparticles was measured using a nanoparticle size analyzer (DLS). Fig.33 ;
[0157] (3) Crystal structure characterization: The obtained starch nanoparticle powder was subjected to XRD scanning at 40 kV and 50 mA using Cu Kα radiation (λ = 0.1542 nm). Fig.34 .
[0158] The starch nanoparticles prepared in this comparative example are Fig.32 SEM images and Fig.33It can be seen from the particle size distribution diagram that a mixed system of rod-shaped starch nanoparticles and ellipsoidal starch nanoparticles was formed under the stirring rearrangement conditions of 70°. Fig.34 The gentle crystal peak in the XRD image indicates that the crystal structure of the sample is weak.
[0159] Comparative Example 2
[0160] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0161] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of corn starch (dry basis) was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0162] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0163] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 50°. The stirring speed was maintained at 1500 rpm during the process;
[0164] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0165] The morphology and structure of the prepared samples were characterized as follows:
[0166] (1) Morphological observation: The obtained strip-shaped starch nanoparticles were passed through a 200-mesh sieve. 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. The suspension was evenly dispersed using a homogenizer and then dropped onto a silicon wafer fixed on a copper stand. After natural drying, the suspension was subjected to gold spraying. The surface morphology of the sample was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3 KV. Fig.35 .
[0167] (2) Particle size measurement: The obtained strip-shaped starch nanoparticles were sieved through a 200-mesh sieve, and 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. After being dispersed evenly using a homogenizer, the particle size distribution of the starch nanoparticles was measured using a nanoparticle size analyzer (DLS). Fig.36 ;
[0168] (3) Crystal structure characterization: The obtained starch nanoparticle powder was subjected to XRD scanning at 40 kV and 50 mA using Cu Kα radiation (λ = 0.1542 nm). Fig.37 .
[0169] The starch nanoparticles prepared in this comparative example are Fig.35 SEM images and Fig.36 It can be seen from the particle size distribution diagram that a mixed system of ellipsoidal starch nanoparticles and spindle-shaped starch nanoparticles was formed under the stirring rearrangement conditions of 50°. Fig.37 The gentle crystal peak in the XRD image indicates that the crystal structure of the sample is weak.
[0170] Comparative Example 3
[0171] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0172] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of corn starch (dry basis) was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0173] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0174] (3) Rearrangement treatment using a paddle stirrer: The polymorphic starch nanoparticle precursor solution was treated with a paddle stirrer for 30 min to induce rearrangement of the starch chain molecules in the solution, thereby achieving the purpose of purifying the system and obtaining a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis was 30°, and the angle between the paddle plane and the plane perpendicular to the rotation axis was 25°. The stirring speed was maintained at 1500 rpm during the process;
[0175] (4) The purified polymorphic starch nanoparticle solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0176] The morphology and structure of the prepared samples were characterized as follows:
[0177] (1) Morphological observation: The obtained strip-shaped starch nanoparticles were passed through a 200-mesh sieve. 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. The suspension was evenly dispersed using a homogenizer and then dropped onto a silicon wafer fixed on a copper stand. After natural drying, the suspension was subjected to gold spraying. The surface morphology of the sample was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3 KV. Fig.38 .
[0178] (2) Particle size measurement: The obtained strip-shaped starch nanoparticles were sieved through a 200-mesh sieve, and 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. After being dispersed evenly using a homogenizer, the particle size distribution of the starch nanoparticles was measured using a nanoparticle size analyzer (DLS). Fig.39 ;
[0179] (3) Crystal structure characterization: The obtained starch nanoparticle powder was subjected to XRD scanning at 40 kV and 50 mA using Cu Kα radiation (λ = 0.1542 nm). Fig.40 .
[0180] The starch nanoparticles prepared in this comparative example are Fig.38 SEM images and Fig.39 It can be seen from the particle size distribution diagram that the starch nanoparticles formed under the stirring rearrangement conditions of 25° are in the form of aggregates. Fig.40 The gentle crystalline peak in the XRD pattern indicates that the crystalline structure of the sample is weak.
[0181] Comparative Example 4
[0182] A method for preparing polymorphic starch nanoparticles, such as Figure 1 As shown, the steps are as follows:
[0183] (1) Preparation of gelatinized starch cluster solution: After 2 g of NaOH particles were completely dissolved in 100 mL of deionized water, 5 g of corn starch (dry basis) was dispersed in the sodium hydroxide solution and placed in a 95 °C water bath for gelatinization for 10 min. During the process, the magnetic stirring speed was maintained at 200 rpm, and then cooled to room temperature to form a 5% weight-volume starch cluster solution.
[0184] (2) Alcohol precipitation treatment: 100 mL of anhydrous ethanol was dripped into the starch cluster solution prepared in step (1) at a rate of 30 mL / min, and the stirring speed was maintained at 1500 rpm during the process to form a polymorphic starch nanoparticle precursor solution;
[0185] (3) The polymorphic starch nanoparticle precursor solution was centrifuged, the precipitate was washed with anhydrous ethanol and centrifuged again to obtain a final precipitate, the final precipitate was freeze-dried, and then ground to obtain purified strip-shaped starch nanoparticles; the conditions for the two centrifugation treatments were centrifugation at 8000 rpm for 10 min; the conditions for the freeze-drying treatment were: vacuum drying at -60°C for 2 days; and the conditions for the grinding were: grinding at 15000 rpm for 90 s using a grinder.
[0186] The morphology and structure of the prepared samples were characterized as follows:
[0187] (1) Morphological observation: The obtained strip-shaped starch nanoparticles were passed through a 200-mesh sieve. 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. The suspension was evenly dispersed using a homogenizer and then dropped onto a silicon wafer fixed on a copper stand. After natural drying, the suspension was subjected to gold spraying. The surface morphology of the sample was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3 KV. Fig.41 .
[0188] (2) Particle size measurement: The obtained strip-shaped starch nanoparticles were sieved through a 200-mesh sieve, and 25 mg of the sieved particles were dissolved in 25 mL of deionized water to prepare a suspension. After being dispersed evenly using a homogenizer, the particle size distribution of the starch nanoparticles was measured using a nanoparticle size analyzer (DLS). Fig.42 ;
[0189] (3) Crystal structure characterization: The obtained starch nanoparticle powder was subjected to XRD scanning at 40 kV and 50 mA using Cu Kα radiation (λ = 0.1542 nm). Fig.43 .
[0190] The starch nanoparticles prepared in this comparative example are Fig.41 SEM images and Fig.42 It can be seen from the particle size distribution diagram that the rearrangement treatment without stirring formed irregularly shaped aggregated particles. Fig.43 The gentle crystalline peak in the XRD pattern indicates that the crystalline structure of the sample is weak.
[0191] It can be seen from the above examples and comparative examples that the stirring rearrangement process is particularly critical for the transformation of the starch nanoparticle morphology, the optimization of the crystal structure and the purification of the system. Starch granules are fully gelatinized in hot alkaline solutions, and the starch chains unfold with the collapse of the crystal structure. The exposed molecular chains are subjected to the homogenous shear force of stirring during the subsequent alcohol precipitation process, and the glycosidic bonds are non-specifically broken to form starch cluster units of varying sizes with activated hydroxyl groups. Under the action of anti-solvent anhydrous ethanol, the starch clusters immediately form helical complexes, and the single helical structure is further arranged and folded into a layered semi-crystalline structure in a specific orientation. The subsequent short-term stirring rearrangement optimizes the crystal structure of the starch nanoparticles, giving them a higher relative crystallinity and crystal density; the particle size distribution curves all show a clear bimodal type, and the SEM images of the embodiments confirm the axisymmetric strip morphology of the starch nanoparticles. Although Comparative Examples 1, 2, and 3 also have obvious strip-shaped particles, they are accompanied by more irregular pastes, showing a mixed system of polymorphic starch nanoparticles with a weaker crystalline structure, which shows the necessity of controlling the angle between the paddle blade of the paddle stirrer and the plane perpendicular to the rotating axis. Comparative Example 4 presents irregularly shaped aggregated particles, and the XRD diagram shows an amorphous peak, which shows the necessity of the rearrangement process for the formation of strip-shaped starch nanoparticles and the improvement of the crystalline structure. The morphology of starch nanoparticles changes with the change of the angle between the paddle blade of the stirrer and the plane perpendicular to the rotating axis, and this change has a similar trend in different types of starch: rod-shaped at 30-48°, ellipsoidal at 51-69°, and spindle-shaped at 72-90°, indicating that by controlling the angle between the paddle blade of the paddle stirrer and the plane perpendicular to the rotating axis, strip-shaped starch nanoparticles with controllable morphology and high relative crystallinity can be designed and produced.
[0192] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing polymorphic starch nanoparticles, characterized in that: The steps include: (1) Disperse 5 g of starch in 100 mL of 0.5 M sodium hydroxide solution for gelatinization in a water bath and cool to room temperature to form a starch cluster solution; (2) subjecting the starch cluster solution to alcohol precipitation to form a polymorphic starch nanoparticle precursor solution; (3) using a paddle stirrer to stir and rearrange the mixture to obtain a purified polymorphic starch nanoparticle solution; the angle between the midline of the paddle of the paddle stirrer and the plane perpendicular to the rotation axis is 30°, and the stirring speed is 200-1500 rpm; (4) centrifuging the purified polymorphic starch nanoparticle solution, washing the precipitate with anhydrous ethanol and centrifuging it again to obtain a final precipitate, freeze-drying the final precipitate, and then grinding it to obtain purified strip-shaped starch nanoparticles; The strip-shaped starch nanoparticles are one of rod-shaped, ellipsoid-shaped, and spindle-shaped. When the angle between the blade plane and the plane perpendicular to the rotation axis is 72~90°, rod-shaped strip-shaped starch nanoparticles are produced. When the angle between the blade plane and the plane perpendicular to the rotation axis is 51~69°, ellipsoid-shaped strip-shaped starch nanoparticles are produced. When the angle between the blade plane and the plane perpendicular to the rotation axis is 30~48°, spindle-shaped strip-shaped starch nanoparticles are produced.
2. The method according to claim 1, characterized in that The starch is one or more of corn starch, rice starch, wheat starch, sweet potato starch, cassava starch, sweet potato starch and potato starch.
3. The method according to claim 1, characterized in that The water bath gelatinization conditions are as follows: the sodium hydroxide solution of starch is placed in a water bath at 65-95° C., while the magnetic stirring speed is maintained at 200-800 rpm.
4. The method according to claim 1, characterized in that: The alcohol precipitation treatment is as follows: anhydrous ethanol is dripped into the starch cluster solution at a speed of 5-30 mL / min, the volume ratio of anhydrous ethanol to the starch cluster solution is 1:1, and the stirring speed is maintained at 200-1500 rpm during the alcohol precipitation treatment.
5. The method according to claim 1, characterized in that The centrifugal conditions are as follows: the centrifugal speed is 4000-8000 rpm, and the centrifugal time is 10-20 min.
6. The method according to claim 1, characterized in that The freeze-drying treatment conditions are: vacuum drying at -60 to -40°C.
7. The method according to claim 1, characterized in that The grinding conditions are: grinding with a grinder at 15000 rpm for 90 seconds.
Citation Information
Patent Citations
Preparation method of starch nanospheres with uniform size
CN116813943A
Cellulose ethers
GB999587A